Thyroid Function and Autoimmunity Versus Number of Pregnancies - B Boufas; A Vryonidou; G Mastorkos; I Ilias (JRI, 2016)
Background: Thyroid autoimmunity may be linked to infertility, in both thyrotropin (TSH)-dependent and TSH-independent fashion. The aim of the present study was to assess this presumed reciprocal relationship of thyroid autoimmunity and pregnancy. Methods: TSH and antithyroid peroxidase autoantibodies (anti-TPO) were evaluated retrospectively over an eight-year period in 444 Greek women who had previously none or at least one pregnancy (>28 weeks). Statistics were done with analysis of covariance (ANCOVA) and the Chi square test. Results: Thyrotropin was higher in women with one pregnancy and lower in those with two or more pregnancies compared to women with no pregnancies. Furthermore, significantly more women with no pregnancies were anti-TPO (+), compared to women with one or those with at least two pregnancies. Conclusion: Because pregnancy might contribute to the development of thyroid autoimmunity, women should be monitored for development of thyroid autoimmunity long after their pregnancies, even after an uneventful first conception, pregnancy and delivery of a live infant.